"You Obviously Just Have to Put on a Brave Face": A Qualitative Study of the Experiences and Coping Styles of Men With Rheumatoid Arthritis. Issue 3 (March 2017) - Flurey, Caroline A.; Hewlett, Sarah; Rodham, Karen; White, Alan; Noddings, Robert; Kirwan, John R.
Abstract : Objective: To explore the experiences, coping styles, and support preferences of male rheumatoid arthritis (RA) patients. Methods: Six focus groups comprised 22 men with RA. Transcripts were analyzed using inductive thematic analysis. Results: Three overarching themes describe the experiences, coping styles, and support preferences of men with RA. In "challenges to masculinity, " the men described a "reduction in strength and abilities, " which can lead to loss of independence, "challenges to masculine identity and role, " and "loss of power and control." Coping by "getting through life with RA" meant dealing with RA by "just getting on with it, " "information seeking, " engaging in "destructive behaviors, " and "withdrawing socially." Preferred "sources of support" tended not to include friends, as they were perceived to lack understanding or support. For acceptable support the men reported a preference for information‐giving sessions rather than a discussion group, but there was no agreement on whether these should be mixed‐sex or men only, or who should run the sessions. Conclusion: Male patients reported a range of coping styles and support preferences to address their experiences of living with RA, many of which may not be shared with women. Further research is needed to investigate whether these findings exist in a larger sample and whether the support preferences of men with RA are broadly different from those of women with RA to decide whether there is a clinical need to design a service for the potentially different needs of men.